2004
DOI: 10.1167/iovs.03-1039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Erythropoietin Axotomy-Induced Apoptosis in Rat Retinal Ganglion Cells

Abstract: These data support a potential role for EPO as a therapeutic molecule against predominantly apoptotic neuronal cell death in the context of glaucoma or neurodegenerative diseases and delineate the PI-3-K/Akt pathway as the predominant mediator of EPO neuroprotection in this in vivo paradigm of neuronal cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
144
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 62 publications
10
144
1
2
Order By: Relevance
“…10 U/mL) did not show stronger protective effects. Several studies have confirmed this particular dose-response behavior of EPO in vivo [17,18] , which might have relevance to the design of the upcoming clinical trials. As the recent human stroke study has demonstrated, EPO has beneficial effect on neurons in the context of cerebral ischemia [19] .…”
Section: Discussionsupporting
confidence: 54%
“…10 U/mL) did not show stronger protective effects. Several studies have confirmed this particular dose-response behavior of EPO in vivo [17,18] , which might have relevance to the design of the upcoming clinical trials. As the recent human stroke study has demonstrated, EPO has beneficial effect on neurons in the context of cerebral ischemia [19] .…”
Section: Discussionsupporting
confidence: 54%
“…Antiapoptotic effects of Epo on immunopurified RGCs have been demonstrated recently in vitro, indicating that Epo acts directly on these neurons. 48 Additionally, in this study intravitreal applications of Epo were shown to prevent RGC death after surgical transection of the ON. As the intravitreal approach causes structural damage to the rat eye after repetitive applications, we used systemic applications of Epo in our present study.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies showed that PI 3-kinase/Akt pathway plays a major role in mediating the survival response of retinal ganglion cells after axotomy to a variety of growth factors. [12][13][14] In addition, apoptosis of retinal neurons induced by serum deprivation was reduced by insulin via activating the PI 3-kinase/Akt pathway. 15 Furthermore, retinal PI 3-kinase/Akt signalling pathway was activated by optic nerve clamping and had a neuroprotective effect on injured retinal ganglion cells.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16] Several studies showed that Cox-2 functions as a survival factor by protecting cells from apoptosis. [17][18][19][20][21] Overexpression of Mcl-1, a member of the Bcl-2 family, 22 delays apoptosis by a broad array of agents.…”
mentioning
confidence: 99%